Caribbean Immigrant Youths' Ethnic Identity and Academic Achievement: The Role of Academic Beliefs. Issue 3 (April 2022) - Smith, Naila A.; Thelamour, Barbara; Booth, Margaret X.
Ethnic identity (EI) can facilitate racially and ethnically marginalized youths' academic achievement but the mediating process by which it exerts its influence is unclear. This study examines how EI is associated with academic achievement through academic beliefs in a sample of Caribbean first and second generation immigrant adolescents whose identities are connected to cultural groups outside of the U.S. Youth ( N  = 128; 12–18 years old, M  = 16.32, SD  = 1.81; 69.3% second generation; 58.6% Black) reported on their EI affirmation and belonging and EI achievement, academic self-efficacy, academic aspirations, and grades. Results of our serial mediation model showed that stronger EI achievement was associated with higher academic self-efficacy and in turn higher academic aspirations, and higher grades. These findings offer potential targets (i.e., academic self-beliefs) for supporting the academic success of Black and Hispanic Caribbean immigrant students and have implications for their boosting educational outcomes.